Basal salivary cortisol levels in elite athletes: is there any variation depending on sport discipline? - Mauri, C.; Bertone, M.; Fiorella, P. L.; Sardella, F.; Tranquilli, C.; Faina, M. (Archivos de medicina del deporte, 2008)
Cortisol is a corticosteroid hormone produced in the Zona fasciculata of the adrenal gland cortex. It is involved in the response to stress. Cortisol levels undergo diurnal variation, with the highest level present in the early morning, and the lowest around midnight, 3-5 hours after sleep onset. Given sport as a major stressor in elite athletes life, it seems sensible to study cortisol levels in such a population. Aim of this study was the assessment of possible differences in basal salivary cortisol levels between male and female elite athletes and, within these samples, differences depending on the specific sport discipline practiced. This study covers a two years period (2006-2007). Its sample size refers to the number of cortisol samples and not to the number of athletes involved, which means the same subject may have given more than one sample. 806 salivary samples were collected in Salivette test tubes among Olympic teams of different disciplines. These samples were frozen and stored at -70°C until testing. A fully automated chemiluminescence system (Salivary Cortisol ELISA kit, DRG Diagnostics, Germany) was used to analyze the samples. Data obtained were evaluated both through parametric (t Test) and non parametric statistics (Wilcoxon Test), depending on data distribution. Results are presented as mean ± standard deviation; differences were considered significant at P<0.01. A statistical significant difference was evident in the comparison between male (n.627 samples) and female (n.179 samples) population (8.0±3.6 vs 8.7±3.1 ng/ml respectively, p<0,01). Within the male and female populations further comparisons were led between each sport discipline. Statistical significances are presented in the Table 1. There are no apparent clinical or physiological reasons supporting the statistically significant difference found between the whole male and female populations. It might come from the two populations different sample size. As far as the male group is concerned the Endurance sample always shows significantly lower values than the other two groups, this could be considered as an expression of different adaptive responses to a training with volume prevailing over intensity. In the female group statistically significant differences were found in all the comparisons. The more intensity overcomes volume in the training, the higher the basal cortisol levels become. Given the data in this study it is possible to suggest that basal cortisol levels follow a direct adaptation to the workload intensity.